José Ángel Valente’s Poetic Word - Guillermo Aguirre Martínez (Castilla: Estudios de Literatura, 2014)
The poetic word, in the view of José Ángel Valente, owns different values and roles that distinguish it from the conventional language. In this way, opposite to the servile nature of the latter -subject to market relationships-, the poetic word works as a Logos due to its creative power. This power comes from its capacity to join the rational order with the emotional one. The poetic word, in accordance with José Ángel Valente, has sacred qualities based on its relation with the transcendental. Accordingly, this sacred language does not participate in a causal logic. From this point of view, we can understand the role of the poet as a struggle for access to deeper and truer degree of reality. Throughout the next pages, we will study this role of the poetic language.